Cold plasma treated thyme essential oil/silk fibroin nanofibers against Salmonella Typhimurium in poultry meat. (September 2019) - Lin, Lin; Liao, Xue; Cui, Haiying
Graphical abstract: Highlights: Thyme essential oil (TO)/silk fibroin (SF) nanofibers were fabricated. After cold plasma treatment, the release rate of TO from nanofibers was improved. The nanofibers showed high antibacterial activity against S. typhimurium on poultry meat. Abstract: Silk fibroin is widely used in the medical field as an electrospinning material, but there are few reports on the application of silk fibroin nanofibers encapsulating antibacterial essential oil as active antibacterial packaging in food. This study aims to fabricate cold plasma treated thyme essential oil (TO)/silk fibroin (SF) nanofibers to inhibit Salmonella Typhimurium in poultry meat. Firstly, antimicrobial activity and mechanism of TO against Salmonella Typhimurium was assessed. Subsequently, viscoelastic properties of spinning solutions and properties of nanofibers which included nanofibers stability, hydration, barrier and mechanical properties were studied to screen good performance nanofibers. Further, cold plasma was applied to implement the surface modification of TO/SF nanofibers. The results showed that the TO release amount of plasma-TO/SF nanofibers improved obviously after cold plasma treatment, leading to higher antibacterial activity of plasma-TO/SF nanofibers than TO/SF nanofibers. After plasma-TO/SF nanofibers treatment, the number of Salmonella Typhimurium in chicken meat and duck meat decreased by 6.1 and 6.06 Log CFU/g compared with control group at 25 °C, respectively. Overall, this study indicated that plasma-TO/SF nanofibers membrane was an effective antimicrobial packaging to increase shelf life of foods, which had a broad prospect in the field of food preservation.